Soliton for optical sensor: numerical studies - Mohamad, Azam; Abd Mubin, Mohamad Helmi; Yaacob, Siti Azwani; Roslan, Muhammad Sufi; Abdullah, Munzir (Smart Manufacturing Research Institute (SMRI), 2025)
Soliton for optical sensors is essentially a new way for overcoming a sensing sensitivity constraint. High sensitivity in terms of device accuracy is in demand nowadays, and it plays an important part in achieving improved performance. Due to this constraint, we observe that the largest sensing limitation originates from the input optical pulse that travels inside the waveguide, which governs pulse reduction before sensor testing. As a result, the development of optical soliton is required to circumvent this limitation. In the present work, we proposed design recommendations for soliton-based optical sensors by numerically investigating soliton production in a silicon channel waveguide. The effects of nonlinearity, dispersion, and waveguide geometry on soliton stability were examined. The findings indicate that adjusting the waveguide thickness to 300 nm guarantees single-mode operation at 1.55 µm, resulting in an anomalous dispersion regime with group velocity dispersion of –26.83 ps²·mm⁻¹ and a group index of 6.96. Stable solitary pulse propagation was made possible by the calculated soliton order of 0.84, which indicates operation near the basic soliton regime. At waveguide length of 8.7 mm, where dispersive and nonlinear effects are well balanced, maximum transmission took place, but soliton production required a minimum length of ~4.5 mm. At this length, the soliton retained its intensity and pulse waveform, indicating strong propagation conditions. These findings provide a mathematical framework for connecting soliton order, dispersion length, and nonlinear length to sensor performance. The findings show that maintaining pristine soliton output within a silicon waveguide is a straightforward strategy to improve the sensitivity as well as performance of next-generation optical sensors.